2021
DOI: 10.1039/d1ra04270j
|View full text |Cite
|
Sign up to set email alerts
|

Strongly reduced lattice thermal conductivity in Sn-doped rare-earth (M) filled skutterudites MxCo4Sb12−ySny, promoted by Sb–Sn disordering and phase segregation

Abstract: Three effects act as phonon scatterers: rattling of M at 8a cages, phase segregation, and intrinsic disorder introduced by Sn substitution, resulting in minimum k values. High filling fraction in Sn-doped phases pave the way to tune the carrier density in skutterudites.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(11 citation statements)
references
References 51 publications
(97 reference statements)
2
9
0
Order By: Relevance
“…The main insight is that the electronic transport in this compound is limited by acoustic phonon scattering, an effect that can be noted by the decrease in the weighted mobility with temperature following a 𝑇 / relation. The weighted mobility of this Gd-filled derivative is higher than that observed for other filled skutterudites prepared by the same method [50]. Taking this into account, our samples may have presented a lower carrier concentration than expected, while the Seebeck coefficient was not as enhanced by the band convergence as in another higher-filling-fraction Gd Co4Sb12.…”
Section: Thermoelectric Performancementioning
confidence: 47%
“…The main insight is that the electronic transport in this compound is limited by acoustic phonon scattering, an effect that can be noted by the decrease in the weighted mobility with temperature following a 𝑇 / relation. The weighted mobility of this Gd-filled derivative is higher than that observed for other filled skutterudites prepared by the same method [50]. Taking this into account, our samples may have presented a lower carrier concentration than expected, while the Seebeck coefficient was not as enhanced by the band convergence as in another higher-filling-fraction Gd Co4Sb12.…”
Section: Thermoelectric Performancementioning
confidence: 47%
“…The main insight is that the electronic transport in this compound is limited by acoustic phonon scattering, an effect that can be noted by the decrease of the weighted mobility with temperature following a 𝑇 −3/2 relation. The weighted mobility of this Gd-filled derivative is comparatively higher than that of other filled skutterudites prepared by the same method [45]. Taking this into account, our samples may present a lower carrier concentration than expected, while the Seebeck coefficient is not as enhanced by band convergence as in other higher filling-fraction Gd-Co4Sb12.…”
Section: T [ K ]mentioning
confidence: 50%
“…At T ∼ 640 K, S tends to zero, and it reaches a value of 23.33 μV/K at 675 K, indicating p-type characteristics. The transition from n- to p-type characteristics is attributed to the bipolar conduction assisted by temperature-driven minority carrier excitations. Typically, the contribution from both types of charge carriers to the Seebeck coefficient ( S ) can be given by the following equation, s = S e σ e + S h σ h σ h + σ e where e and h indicate the contribution from electrons and holes, respectively. In skutterudites, a suitable filler in the void sites or proper doping at the Co/Sb sites can alter the charge carriers.…”
Section: Thermoelectric Propertiesmentioning
confidence: 99%
“…Similarly, rare-earth-doped n-type M 0.5 Co 4 Sb 11.6 Sn 0.4 (M = La, Ce, and Yb) and Ce 0.5 Co 4 Sb 12−y Sn y , (with y = 0.2, 0.4, 1) have been examined for thermoelectric applications, and the low thermal conductivity of 1.9 W/(m•K) for Yb 0.5 Co 4 Sb 11.6 Sn 0.4 was caused by the additional phonon scattering from Sb−Sn disordering. 41 It was reported that an element with heavy mass, smaller ionic radii, and a high filling fraction can be regarded as an efficient filler that significantly reduces thermal conductivity. Moreover, a higher fraction of void filling could initiate a noticeable enhancement in the electrical conductivity.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation